Upaya Pemerintahan Desa Dalam Penciptaan ProdukYang Kompetitif(Studi Kasus Pada Industri Krecek Di Gladagsari Kecamatan Ampel Kabupaten Boyolali - Yulianti, Tri, Agus Prasetyo, S.Pd, M.Pd (2016)
The purpose of this study was to describe the village governance efforts in the creation of compertitive products in the village Gladagsari Ampel Boyolali District of the following problems and solutions. This research was qualitative. Data collection techniques used in this research is by interview, observation, and study documents or archives. Techniques for testing the validity or authenticity of data is done by means of triangulation. The data triangulation techniques are using data reduction, data presentation, and conclusion. Results show that: 1) the village government has been carrying out its responsibilities in accordance with aspects of governance (good governance), especially in the creation of a competitive market. 2) although it tried to give the program-the program optimally but there are still constraints in implementing governance government in the creation of a competitive market starting from the village is lacking in disseminating information and guidance to the owners of domestic industry, but it comes up from the owners domestic industry less attention to product quality, they cheat and do not have a business license. Solutions to overcome the constraints of village governance in the creation of a competitive market is to continue to improve socialization, conduct surveillance and asking owners of domestic industries to soon have a business license.